Utveckling av Trailplate - En skyddande innersula - Johansson, Erik; von Sparr, Hampus (My University, 2012)
The project aimed to develop a protective and stabilizing insole called Trailplate for soft and light shoes. The demand came primarily from off-road runners in France, Switzerland, and Austria. The project was carried out at Icebug, a company that develops shoes mainly for rough terrain. The main focus has been on the trailplate which is designed to fit several different shoes. Torsional stiffness and bending resistance were the main objectives. To improve the existing insole, a material with the right features was required. The optimal design would meet the above functional requirements and provide comfort. Due to financial aspects sizing was also optimized. The results show that that the material of the insole must have a Young's modulus of at least 5 GPa to reduce deflection while maintaining a minimum thickness of 2 mm. The choice of material was also affected by costs and production aspects. While carbon was found to be a material with very desirable characteristics its high cost shifted to focus to hard plastic. The final recommendation for Icebug was Polyoxymethylene (POM) because it had the desired qualities with the added bonus of being cost effective. The final design included a flexible forefoot that follows the foots flex line (the metatarsal-phalangeal joint), ridges in the forefoot to prevent deflection, and a hole at the heel to increase the foots natural suppression. The product will help off-road runners in rocky terrain by offering support and protection for their feet.
Keywords: Maskinteknik; Konstruktionsmaterial; Innovation och entreprenörskap (nyttiggörande); Materialvetenskap; Produktion; Mechanical Engineering; Construction materials; Innovation & Entrepreneurship; Materials Science; Production